Cognitive behavioral therapy for depression in Japanese Parkinson's disease patients: a pilot study - Shinmei I (Dove Medical Press, 2016)
Issei Shinmei,1,2 Kei Kobayashi,3 Yuki Oe,1 Yuriko Takagishi,1,4 Ayako Kanie,1 Masaya Ito,1 Yoshitake Takebayashi,1,5 Miho Murata,3 Masaru Horikoshi,1 Roseanne D Dobkin6 1National Center for Cognitive Behavioral Therapy and Research, National Center of Neurology and Psychiatry, Tokyo, Japan; 2Department of Neuropsychiatry, Interdisciplinary Graduate School of Medicine and Engineering, University of Yamanashi, Yamanashi, Japan; 3Department of Neurology, National Center of Neurology and Psychiatry, Tokyo, Japan; 4Department of Psychology, Surugadai University, Saitama, Japan; 5Risk Analysis Research Center, The Institute of Statistical Mathematics, Tokyo, Japan; 6Department of Psychiatry, Rutgers-Robert Wood Johnson Medical school, NJ, USA Objectives: This study evaluated the feasibility of cognitive behavioral therapy (CBT) for Japanese Parkinson’s disease (PD) patients with depression. To increase cultural acceptability, we developed the CBT program using manga, a type of Japanese comic novel.Methods: Participants included 19 non-demented PD patients who had depressive symptoms (GRID-Hamilton Rating Scale for Depression score ≥8). A CBT program comprising six sessions was individually administered. We evaluated the feasibility and safety of the CBT program in terms of the dropout rate and occurrence of adverse events. The primary outcome was depressive symptom reduction in the GRID-Hamilton Rating Scale for Depression upon completion of CBT. Secondary outcomes included changes in the self-report measures of depression (Beck Depression Inventory-II, Hospital Anxiety and Depression Scale-Depression), anxiety (Hospital Anxiety and Depression Scale-Anxiety, State and Trait Anxiety Inventory, Overall Anxiety Severity and Impairment Scale), functional impairment, and quality of life (Medical Outcomes Study 36-Item Short-Form Health Survey).Results: Of the 19 participants (mean age =63.8 years, standard deviation [SD] =9.9 years; mean Hohen–Yahr score =1.7, SD =0.8), one patient (5%) withdrew. No severe adverse event was observed. The patients reported significant improvements in depression (Hedges’ g =-1.02, 95% confidence interval =-1.62 to -0.39). The effects were maintained over a 3-month follow-up period. Most of the secondary outcome measurements showed a small-to-moderate but nonsignificant effect size from baseline to post-intervention.Conclusion: This study provides preliminary evidence that CBT is feasible among Japanese PD patients with depression. Similar approaches may be effective for people with PD from other cultural backgrounds. The results warrant replication in a randomized controlled trial. Keywords: CBT, anxiety, Japan, dPD, comorbidity